2001
DOI: 10.1046/j.1365-2516.2001.00557.x
|View full text |Cite
|
Sign up to set email alerts
|

Complications of central venous catheters in patients with haemophilia and inhibitors

Abstract: We report our clinical experience with central venous catheters (CVCs) in 15 patients with haemophilia who, in total, had 34 catheters inserted. Eighteen devices were Hickman, six were Port-A-Cath and 10 were nontunnelled catheters (one Quinton, seven antecubital, one jugular and one subclavian vein access). All patients had factor VIII/IX inhibitors at the time of insertion. The mean age at operation was 8.8 years (range 16 months-39 years). Eight of the 15 patients (26/34 implanted catheters, 76%) presented … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(55 citation statements)
references
References 18 publications
0
54
0
1
Order By: Relevance
“…Other studies have supported these results [7,8]. Morado et al [9] reported a case series of 34 central venous catheter insertions in 15 children with hemophilia and factor VIII/IX inhibitors. Peri-catheter bleeding was noted in seven procedures in six patients requiring substantive treatment for several days.…”
Section: Discussionmentioning
confidence: 78%
“…Other studies have supported these results [7,8]. Morado et al [9] reported a case series of 34 central venous catheter insertions in 15 children with hemophilia and factor VIII/IX inhibitors. Peri-catheter bleeding was noted in seven procedures in six patients requiring substantive treatment for several days.…”
Section: Discussionmentioning
confidence: 78%
“…The patients also risk having other (severe) bleeds that could have an impact on their quality of life. The benefit of starting treatment early with infusions more than once weekly to keep a higher trough level has to be balanced against the need for a central venous line and the risk for complications, especially in patients with a mild bleeding phenotype [30,31]. In a survey of 140 Swedish patients with severe or moderate haemophilia, seven patients were identified with an episode of ICH [29].…”
Section: Discussionmentioning
confidence: 99%
“…This standardized form of expressing the infection rate is to be encouraged in the future. Infection developed in 15 of 34 catheters (44%), and four patients had more than one episode of infection -representing an infection rate of 0.1 per 1000 catheter days [25]. In a recent study from the Royal Free Hospital in London, 10 episodes of infection were reported in six of 11 catheters (54%), necessitating removal of five after a median time of 18 months (range, 2-29 months) [24].…”
Section: Catheter-related Complicationsmentioning
confidence: 98%